Retrospective study of polytrauma patients’s medical records that presented abdominal trauma, comperad to abdominal trauma and extra-abdominal injuries - Coutinho, Izadora Gabriela; Crema, Thiago Henriqque; Petta, Bruno Felipe Viotto; Fontes, Carlos Edmundo Rodrigues (Acta Scientiarum. Health Sciences, 2021)
This study sought to retrospectively assess the relationship between intra and extra-abdominal injuries in polytrauma patients undergoing laparotomy at the Regional University Hospital of Maringá between 2017 and 2018.This study was based on 111 electronic medical records from the Brazilian public health system “SUS”, admitted to the hospital due to trauma and undergoing laparotomy, comparing two groups: abdominal injury without extra-abdominal injury (WoEI) and abdominal injury with extra-abdominal injury (WiEI).A total of 111 medical records were analyzed, 57 from 2017 and 54 from 2018. Of these 111records, 43 (39%) were trauma victims with only abdominal injuries and 68 (61%) trauma victims with abdominal and extra-abdominalinjuries. Most patients were male (85%), with an average age of 33 years, ranging from 14 to 87 years. In statistical analysis, according to the T-test, there was significance (p > 0.05) between the WoEI and WiEI groups for data collected regarding death rates and hospitalization days. As for the morbidity rate and difference between genders (male and female), there was no statistical significance (p < 0.05). Polytrauma patients are exposed to greater kinetic energy, with more severe conditions and therefore required more in-hospital care.